Curriculum 2.0 and student content-based language pedagogy. (August 2019) - Zhong, Yong; Tan, Honghui; Peng, Yi
Abstract: This paper reports on an action research project designed to develop and integrate a new conceptual learning and teaching approach into four language-related courses in an Australian university. Being named Curriculum 2.0 after Web 2.0, the approach places the production, sharing and learning of student content at the centre. In this paper, we recount the project, focusing on how its aims were methodically pursued through reflective experiments to incorporate student content-based pedagogy into the selected courses. Among others, three major actions will be discussed, namely segmenting content, building a content bank and developing an equitable system for assessing individually created content, which proved effective in implementing the new approach. The course and outcomes of the project, to be presented in this paper, will inform the continuing evolution of the scholarship of language learning and teaching. Highlights: Curriculum 2.0 is informed by Web 2.0. Curriculum 2.0 is characterized by creation, sharing and learning of student content, which enable a transformational learning experience, thus modernising tertiary language courses and marking the next step in the evolution from teacher-centredness to student-centredness. Systematic creation, segmentation and assessment of student content are instrumental to the institution of student content. Through trial in real-life language and related courses in a reputable Australian university, Curriculum 2.0 proved effective and engaging for translation and interpreting courses and was well received by learners. Further research is required for it to work in dedicated language courses.